Alteration processes in the CV chondrite parent body based on analysis of NWA 2086 meteorite. (17th August 2014) - Kereszturi, A.; Blumberger, Z.; Józsa, S.; May, Z.; Müller, A.; Szabó, M.; Tóth, M.
Abstract Analysis of the NWA 2086 CV3 chondrite showed a matrix/chondrule ratio of 52%, similar to Bali, Mokoia, and Grosanaja. Nearly twice as many chondrule fragments as intact ones demonstrate that an early fragmentation phase occurred prior to final accretion. After this event, no substantial mechanical change or redeposition is evident. Rims with double‐layered structures were identified around some chondrules, which, in at least one case, is attributed to an accretionary origin. The rim's outer parts with a diffuse appearance were formed by in situ chemical alteration. During this later process, Mg content decreased, Fe content increased, and olivine composition was homogenized, producing a rim composition close to that of the matrix. This alteration occasionally happened along fractures and at confined locations, and was probably produced by fluid interactions. Iron oxides are the best candidate for a small grain‐sized alteration product; however, technical limitations in the available equipment did not allow exact phase identification. These results suggest that NWA 2086 came from a location (possible more deeply buried) in the CV parent body than Mokoia or Bali, and suffered less impact effects—although there is no evidence of sustained thermal alteration. This meteorite may represent a sample of the CV parent asteroid interior and provide a useful basis for comparison with other CV meteorites in the future.